Association of Plasma Progesterone and Pregnancy Associated Glycoproteins in Post-Insemination Conceived and Non-conceived Gir Cows and Jaffarabadi Buffaloes Detected by BovEasy Rapid PD Kits - Devmurari, Yash J; Vala, Karshan B; Parikh, Suryakant S; Vijyeta, Hardipsinh P; Dhami, Arjan J (Indian Journal of Veterinary Sciences and Biotechnology, 2026)
This research focused on healthy 75 Gir cows and 75 Jaffarabadi buffaloes, 60-65 days postpartum that were inseminated during the  detected estrus and did not return to repeat estrus till day 22 post-AI. They underwent pregnancy diagnosis by plasma progesterone  on Days 21, 28, 36, and 45; pregnancy-associated glycoprotein (PAG) on Days 28, and 36 post-AI; PAG based BovEasy rapid PD kits  on day 28 and 32, and per rectal confirmation on day 45 post-AI. The study assessed and compared conception rates, and the levels  of progesterone and PAG by RIA and ELISA, respectively, in conceived and non-conceived animals. The BovEasy bovine rapid PD kits  showed very high (100%) accuracy, sensitivity, and specificity in detecting early pregnancy. In all 37 cows & 25 buffaloes were found  pregnant by day 32 with PD kits, and the overall actual pregnancy rate at day 45 was 36.7% (55/150,) indicating 4.7% (7/150) embryonic  mortality. There was a significant increase in plasma P4 levels in both cows and buffaloes from Day 21 (2.92 ± 0.27 and 2.40 ± 0.23 ng/ mL) to Day 45 (7.61 ± 0.71 and 5.75 ± 0.67 ng/mL) and PAG from day 28 (5.27 ± 0.87 and 4.48 ± 0.9 ng/mL) to day 36 (9.93 ± 1.63 and  6.96 ± 1.39 ng/mL) in conceived animals, while in non-conceived animals the P4 was unstable, with significant fluctuations over the days  measured, but PAG values always remained below 1 ng/mL. In both the species, a highly significant differences (p
Keywords: BovEasy rapid pregnancy kit, Bovines, Correlations, PAG, Plasma progesterone, Pregnancy status